2019
DOI: 10.1101/560995
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AngularQA: Protein Model Quality Assessment with LSTM Networks

Abstract: Quality Assessment (QA) plays an important role in protein structure prediction. Traditional protein QA methods suffer from searching databases or comparing with other models for making predictions, which usually fail. We propose a novel protein single-model QA method which is built on a new representation that converts raw atom information into a series of carbon-alpha (Cα) atoms with side-chain information, defined by their dihedral angles and bond lengths to the prior residue. An LSTM network is used to pre… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…ACC, MCC, SN, and SP values showed that SDM6A comprehensively outperformed i6mA-Pred and iDNA6mA by more than 3.1%–5.8%, 6.3%–11.8%, 0.5%–5.9%, and 5.9%, respectively (Table 3). It is generally assumed that DL methods perform better than do other ML-based algorithms, 32 which has been widely applied in protein structure and function prediction 33, 34, 35, 36, 37, 38, 39. However, SMD6A consistently outperformed the DL-based method, iDNA6mA, on both benchmark and independent datasets, further emphasizing that systematic selection of feature encodings and two-layer ensemble models are essential for improved prediction.…”
Section: Resultsmentioning
confidence: 99%
“…ACC, MCC, SN, and SP values showed that SDM6A comprehensively outperformed i6mA-Pred and iDNA6mA by more than 3.1%–5.8%, 6.3%–11.8%, 0.5%–5.9%, and 5.9%, respectively (Table 3). It is generally assumed that DL methods perform better than do other ML-based algorithms, 32 which has been widely applied in protein structure and function prediction 33, 34, 35, 36, 37, 38, 39. However, SMD6A consistently outperformed the DL-based method, iDNA6mA, on both benchmark and independent datasets, further emphasizing that systematic selection of feature encodings and two-layer ensemble models are essential for improved prediction.…”
Section: Resultsmentioning
confidence: 99%
“…It shows that the predictions of MASS are significantly different to the predictions of QAcon, ProQ3, and SVMQA. We also evaluated our method using 57 targets in CASP13 experiment along with 16 methods participating in CASP13 including ModFOLD7 series [15], FaeNNz, ProQ4 [14], MESHI series, VoroMQA series [44], MULTICOM-NOVEL, Bhattacharya-SingQ, Bhattacharya-Server, PLU-AngularQA [45], and PLU-TopQA (methods having missing models or targets were excluded). The results are shown in Table 3 for stage 2 and Additional file 1: Table S8 for stage 1.…”
Section: Resultsmentioning
confidence: 99%
“…Although the proposed predictor has shown an excellent performance over the other methods, there is still room for improvement. This includes exploration of other ML algorithms such as decision tree-based [31,32] and neural network-based algorithms [33,34,35] on the same dataset, incorporation of novel features and computational approach as implemented in References [36,37,38,39], and increasing the size of the training dataset based on the future experimental data. Furthermore, we implemented our proposed algorithm in the form of user-friendly web-server () for the wider research community to use.…”
Section: Discussionmentioning
confidence: 99%